(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Prenatal screening plays a critical role in the early identification of congenital pathologies, enabling timely intervention and management to improve neonatal outcomes. Congenital anomalies, which affect approximately 3% of live births, can have significant physical, developmental, and psychological impacts on affected children and their families. This article explores the various prenatal screening methods, including ultrasound, maternal serum screening, and non-invasive prenatal testing (NIPT), and their effectiveness in detecting congenital pathologies such as chromosomal abnormalities, neural tube defects, and structural anomalies. The importance of integrating advanced screening technologies with genetic counseling and patient education is emphasized to ensure informed decision-making and optimal care.